Why do we overreact online? - Tho, Li Ming (Personal Money, 2013)
Most of us have seen the controversial "Listen,listen, listen" video shot at a Universiti Utara Malaysia event. For those who haven't,here's the gist. The two protagonists were Bawani KS,a law student at the university, and Sharifah Zohra Jabeen, president of Suara Wanita 1 Malaysia. The former had been raising some points about existing government policies when the latter started berating her, coming up with stunning and quite illogical rants included how animals have problems of their own. The backlash from netizens against Sharifah that followed was ferocious and overwhelming. While many criticised the way she belittled and patronised the student, some went a step further by posting comments that were racist and profanity-laden.